The opportunity of an internationalization process to Brazil: the case of Etai, a french SME - Lorillon, Jean Edern Yves Maurice Marie (2011)
The study had the main objective of providing a French SME with the information needed to analyze the viability of an internationalization process to Brazil, a difficult path strewn with obstacles. Indeed, many French companies are currently willing to enter the Brazilian market, which is seen as great host country offering numerous opportunities for growth and profitability. However the lack of resources and the many difficulties that have to be dealt with during the internationalization process lead SMEs to carefully analyze the opportunity of an international project before trying to enter the foreign market. Thus, academicals papers were used as references to identify and present administrative, economical and cultural elements that could facilitate or hamper the internationalization process. The main administrative issues presented were the international market selection, the mode of internationalization, and the challenges of the internationalization process. As regards economical elements, we presented the main lending technologies available to SMEs and the impact of lending infrastructures in the host country on credit granting. Finally, in order for the SME to understand the lending process, we presented the banks’ point of view when supplying credit to SME. Cultural aspects that could facilitate or hamper the internationalization process are pointed out through academicals concepts such as 'cultural distance' or 'psychic distance'. We argue that gaps between cultures are likely to generate culture-related difficulties or advantages, and that cultural distance is also likely to impact the entry mode chosen by the company in the host country.